Clinical and Biochemical Parameters among Hemodialysis Patients Before and During the Month of Ramadan: Clinical and Biochemical Parameters among Hemodialysis Patients - Qureshi, Abdul Rehman; Ahmad, Farah; Danish, Syed Hassan; Fayyaz, Shafaq (Pakistan Journal of Health Sciences, 2025)
Ramadan fasting among hemodialysis patients is a complex issue in the Muslim world, with varying opinions and outcomes. Objectives: To evaluate clinical and biochemical parameters in hemodialysis patients before and after Ramadan. Methods: This quasi-experimental study was conducted in a private tertiary care hospital in Karachi from March to April 2024. Patients undergoing hemodialysis for more than three months were included, except those who did not consent. Participants were categorized into three groups: complete fasting, intermittent fasting, and non-fasting. Clinical and biochemical parameters were measured before and after Ramadan, including ultra-filtrate, dry weight, potassium, phosphorus, and albumin. Data were analyzed using SPSS version 27.0, with paired t-tests and significance set at p<0.05. Results: 132 patients participated (56.1% male, 43.9% female). Most (90.9%) did not fast, while 5.3% fasted continuously and 8.3% intermittently. Hypertension was the most common comorbidity (47.7%). Ultra-filtrate levels significantly increased in both male and female. Potassium levels rose significantly in female and in patients on thrice-weekly dialysis. Albumin levels declined across all groups. No significant changes were observed in dry weight or phosphorus levels. Conclusions: It was concluded that increased ultra-filtrate and potassium levels post-Ramadan, with albumin declining in most groups. However, the fasting group showed no significant changes, highlighting the need for group-specific monitoring in hemodialysis patients during Ramadan.